The coefficient matrix A is,
![A=\begin{bmatrix}-4 & 10 \\ -1 & 2\end{bmatrix}](https://img.qammunity.org/2023/formulas/mathematics/college/6xhpvk2vw8i38twy5g5j2800zyfoj4gunq.png)
The constant matrix B is,
![B=\begin{bmatrix}-2 \\ -3\end{bmatrix}](https://img.qammunity.org/2023/formulas/mathematics/college/4ih9w7t1ti9b91lp24t3i55bozskhzi82k.png)
We have the equation,
![AX=B](https://img.qammunity.org/2023/formulas/mathematics/college/w8vhgpigm8tn4vqtkq11f0nj3s9jvpktfi.png)
Solving for X, we have,
![\begin{gathered} AX=B \\ X=A^(-1)B \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/a2cfcophsf4rok7d37qx9tuz61r8ypglkz.png)
Now, if we have a 2 x 2 matrix of the form,
![A=\begin{bmatrix}a & b \\ c & d\end{bmatrix}](https://img.qammunity.org/2023/formulas/mathematics/college/4ysg1asiuwziccg3z9q9aepn713sn6bctt.png)
The inverse of this matrix is given by the formula,
![A^(-1)=(1)/(ad-bc)\begin{bmatrix}d & -b \\ -c & a\end{bmatrix}](https://img.qammunity.org/2023/formulas/mathematics/college/cxv2djv218cx2bpdi1izhs4o9g3xtwb2c1.png)
So, let's find the inverse matrix using this formula. Shown below:
![\begin{gathered} A^(-1)=(1)/(ad-bc)\begin{bmatrix}d & -b \\ -c & a\end{bmatrix} \\ A^(-1)=(1)/(-8--10)\begin{bmatrix}2 & -10 \\ 1 & -4\end{bmatrix} \\ A^(-1)=(1)/(2)\begin{bmatrix}2 & -10 \\ 1 & -4\end{bmatrix} \\ A^(-1)=\begin{bmatrix}1 & -5 \\ (1)/(2) & -2\end{bmatrix} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/s822u6i3c6y1npufcsi8d0ygnrfjb59qzu.png)
Now, we calculate X,
![\begin{gathered} X=A^(-1)B \\ X=\begin{bmatrix}1 & -5 \\ (1)/(2) & -2\end{bmatrix}\begin{bmatrix}-2 \\ -3\end{bmatrix} \\ X=\begin{bmatrix}(1)(-2)+(-5)(-3) \\ ((1)/(2))(-2)+(-2)(-3)\end{bmatrix} \\ X=\begin{bmatrix}-2+15 \\ -1+6\end{bmatrix} \\ X=\begin{bmatrix}13 \\ 5\end{bmatrix} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vhxys1b8xjdecyfgf0llx1oit2xdwxga3u.png)
Thus, the solution of the system is >>>
x = 13y = 5